2021
DOI: 10.1101/2021.09.21.21263879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral loads and profile of the patients infected with SARS-CoV-2 Delta, Alpha or R.1 variants in Tokyo

Abstract: The rapid spread of the Delta variant of SARS-CoV-2 became a serious concern worldwide in summer 2021. We examined the copy number and variant types of all SARS-CoV-2-positive patients who visited our hospital from February to August 2021 using PCR tests. Whole genome sequencing was performed for some samples. The R.1 variant (B.1.1.316) was responsible for most infections in March, replacing the previous variant (B.1.1.214); the Alpha (B.1.1.7) variant caused most infections in April and May; and the Delta va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The abovementioned effects on social life and health are also linked with the nature of the COVID‐19 infection situation. SARS‐CoV‐2 developed into different variants of concern with dissimilar transmissibility and effects on infected individuals (Tani‐Sassa et al, 2022). At the time the survey used in this study was collected, the number of new cases was relatively low (Rajatanavin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned effects on social life and health are also linked with the nature of the COVID‐19 infection situation. SARS‐CoV‐2 developed into different variants of concern with dissimilar transmissibility and effects on infected individuals (Tani‐Sassa et al, 2022). At the time the survey used in this study was collected, the number of new cases was relatively low (Rajatanavin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the R.1 variant (the sublineage of B.1.1.316) spread rapidly in Tokyo in March 2021 3 and that the copy numbers of SARS‐CoV‐2 in patients infected with the Delta variant were no higher than those of the R.1 and Alpha variants 4 …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the R.1 variant (the sublineage of B.1.1.316) spread rapidly in Tokyo in March 2021 3 and that the copy numbers of SARS-CoV-2 in patients infected with the Delta variant were no higher than those of the R.1 and Alpha variants. 4 As a possible cause of the stronger transmissibility of the Omicron variant, higher viral loads in the droplets from patients can be considered. To test this hypothesis, the precise copy numbers of viruses in the patient samples were analyzed.…”
mentioning
confidence: 99%
“…The role of different viral loads regarding the SARS‐CoV‐2 variant is less likely because no significant differences in viral loads were observed when compared with wild‐type and Delta‐variant samples or Delta‐ and Omicron‐variant samples. Even lower viral loads of patients infected with the Omicron variant than those of the Delta‐variant infected patients were reported 20–23 …”
Section: Discussionmentioning
confidence: 99%
“…19 As shown in Even lower viral loads of patients infected with the Omicron variant than those of the Delta-variant infected patients were reported. [20][21][22][23] 5 | CONCLUSION…”
Section: The Study Populationmentioning
confidence: 99%